Os institutos federais e o desenvolvimento: perspectivas inclusivas de um educador geógrafo - Stürmer, Arthur Breno (2020)
Development is a multi-faceted, multi-dimensional term that is used to refer to levels, stages, or processes of change, depending on scale, from local to global, and different human activities. Development is also thought of by the economic, social, environmental and educational sectors. However, its relation to education, although not so evident, creates a domain in which development gains new meanings, which are of interest to investigate. With the possibilities of the Federal Institutes of Education, Science and Technology acting in local communities contexts, they are able to promote a type of development through professional and technological education. With the expansion and internalization of the Federal Network of Professional and Technological Education (RFEPCT), new subjects in their territories brought less immediately economic demands. It was necessary to investigate the possibilities of development through the work of the Federal Institutes (FIs) with vulnerable populations. It had been necessary to locate them among the educational practices that could empower subjects in socially vulnerable situations, to map agents, means and strategies have been used to serve such populations and, finally, to map the possibilities of action and incapacities to develop the place and the regional. The investigation focused on official documents from RFEPCT, Federal Institutes as a whole, Farroupilha Federal Institute and campuses, in a backward movement to the coordinations and nuclei. It covers the period from 2006 to 2018, during which time the Federal Institutes' performance has been shaped according to a territorialist perspective. The qualitative approach was based on the critical analysis of developmental conceptions in the Institutes, using the category territory and space in Santos (1978, 1986, 1996, 1998, 1999, 2000, 2002, 2005, 2007, 2008a, 2008b, 2008c, 2016), development in Saquet (2015a, 2015b, 2017), Souza (1995, 1996, 1997, 2003, 2005, 2006, 2008a, 2008b, 2010, 2011, 2013, 2015), Dallabrida (2017), Freire (1959, 2002, 2011, 2012a, 2012b, 2013, 2014, 2016) and education in Brandão (2007) and Libâneo (2012, 2018a, 2018b). The possibility for the Federal Institutes for “development” relies on the plurality of definitions of development, one of which is revealed by the commitment to vulnerable populations. Being in the interface between education and development, the institutes have in inclusive actions, practices capable of generating positive changes in the communities represented by the universe of students served. Through diverse educational strategies, the Inclusive Nuclei stand as territorial agents that favor human territoriality, allowing the conception of a kind of development possible through their own education. In the face of inclusive socio-spatial development, (economic) development goals fall back on the inability to develop local and regional outside of a liberating, empowering pedagogy capable of creating the association of education, territory and development.